Emotional regulation and psychological well-being in operational firefighters - Toaza Caisaguano, Tannia Diana; Pilco Guadalupe , Gina Alexandra (Arandu UTIC, 2025)
Introduction: operational firefighters are personnel trained to face emergencies; therefore, it is necessary to maintain emotional regulation, adaptive and problem-solving skills that favor the mastery of their work activities. The objective of this research was to determine the relationship between emotional regulation and psychological well-being in operational firefighters of the Ambato Fire Department, Ecuador. Methodology: quantitative, descriptive, comparative, correlational and cross-sectional design, working with a sample of 150 firefighters. Emotional regulation was assessed with the Emotional Regulation Questionnaire (ERQ) and psychological well-being with the Ryff Psychological Well-Being Scale. Results: women presented higher levels in both variables. In emotional regulation, 67.9 % of women were at the medium level, compared to 55.7 % of men at the low level. Regarding psychological well-being, 75 % of women showed high levels, in contrast to 63.9 % of men. In addition, a significant positive correlation was observed (r = 0.488, p < 0.001), suggesting that better emotional regulation favors psychological well-being. Gender differences in emotional regulation strategies were also identified: women prefer cognitive reappraisal, whereas men tend to emotional suppression. Conclusions: These findings highlight the importance of fostering emotional regulation skills to improve the mental health of firefighters and open the door to future research on gender differences in this area.